Intra-individual variability in day-to-day and month-to-month measurements of physical activity and sedentary behaviour at work and in leisure-time among Danish adults - E. S. L. Pedersen; I. H. Danquah; C. B. Petersen; J. S. Tolstrup (BMC, 2016)
Abstract Background Accelerometers can obtain precise measurements of movements during the day. However, the individual activity pattern varies from day-to-day and there is limited evidence on measurement days needed to obtain sufficient reliability. The aim of this study was to examine variability in accelerometer derived data on sedentary behaviour and physical activity at work and in leisure-time during week days among Danish office employees. Methods We included control participants (n = 135) from the Take a Stand! Intervention; a cluster randomized controlled trial conducted in 19 offices. Sitting time and physical activity were measured using an ActiGraph GT3X+ fixed on the thigh and data were processed using Acti4 software. Variability was examined for sitting time, standing time, steps and time spent in moderate-to-vigorous physical activity (MVPA) per day by multilevel mixed linear regression modelling. Results Results of this study showed that the number of days needed to obtain a reliability of 80% when measuring sitting time was 4.7 days for work and 5.5 days for leisure time. For physical activity at work, 4.0 days and 4.2 days were required to measure steps and MVPA, respectively. During leisure time, more monitoring time was needed to reliably estimate physical activity (6.8 days for steps and 5.8 days for MVPA). Conclusions The number of measurement days needed to reliably estimate activity patterns was greater for leisure time than for work time. The domain specific variability is of great importance to researchers and health promotion workers planning to use objective measures of sedentary behaviour and physical activity. Trial registration Clinical trials NCT01996176 .